Import Components and Import Multipliers in Australian Economy: World Input-Output Analysis - Muchdie, M.; Kurniawan, H. (International Journal of Economics and Financial Issues, 2018)
This article analysis on import components and import multipliers, using Australian input-output tables 2000, 2005, 2010 and 2014. The results showed that firstly, Australian import components of input were, on average, less than 20 per cent; meaning that input that locally provided were more than 80 per cent. Australian import of input had increased significantly from US$ 47,122 million in 2000 to US$ 14,616 million in 2014. Secondly, Australian imports have been dominated by Sector-8, Sector-13, Sector-24, Sector-25, and Sector-26. Thirdly, Australian imports have been dominated by the USA, Japan, United Kingdom, China and Germany. During 2000-2014, import from Canada, Japan, UK and the USA had declined, but import from China had significantly increased. Finally, highest sectoral import multipliers occurred in Sector-5, Sector-22, Sector-29, Sector-30, Sector-31, and Sector-32, but there was no significant different of import multipliers for country origin of import. Keywords: import components, sectoral import multipliers, spatial import multipliers. JEL Classifications: C67, D57, F17.